Estudo de flambagem em colunas utilizando a técnica de velocimetria por imagem de partículas (PIV) - Rodrigues, Maykmiller Carvalho (2015)
Faced to the complex analysis of structural deformation, buckling effects were studied in steel rectangular hollow bar subjected to axial compressive forces. It worked to quantify the horizontal column deformation using an optical technique, based on images to evaluate the structural behavior. The objective of this study was to use the particle image velocimetry (PIV) technique a non destructive method to study the structures. The test using metallic specimens were performed in the Resistance of Materials and Mechanics of Structure Laboratory of the Federal University of Lavras (UFLA). It evaluated the behavior of metallic columns requested solely by an axial compressive load that caused a buckling effect on the columns. The PIV technique was a pplied to quantify the strain, based on the image analysis to provide and measure the displacement of the structure. With the application of PIV technique, buckling map was provided during the test. It show the different stages during the compressive teste and 1,62mm of the horizontal displacement towards lower inertia was obtained while the displacement obtained by Finite Element was 1,56mm in this same direction. From the resulting vector module was possible to differentiate the stage of the column before and after the critical load of buckling and breaking point thereof. Thus, it was concluded that the PIV technique can be used to measure the column displacement in a plane, which certainly permit its application to monitor structures in use.